Strategi Pemerintah Kota Surabaya Dalam Pengelolaan Sampah Menjadi Energi Listrik - A. Tsani Sabhan Febrian; Sri Wibawani (Faculty of Social Science, Universitas Negeri Padang, 2025)
The purpose of this study is to describe in depth the Strategy of the Surabaya City Government in Managing Waste into Electrical Energy. This study uses a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The focus of this study is based on Geoff Mulgan's Government Strategy theory (Mulgan, 2009): Objectives, Environment, Direction, Action, Learning. The results of the study state that 1) Objectives, to reduce the amount of waste generated at the Benowo Surabaya TPA. 2) Environment, which influences the implementation of this strategy, namely external factors from the private sector PT Sumber Organik as the manager of the TPA and the internal environment, the Surabaya City Government which prepares and regulates the implementation of waste management into electrical energy. 3) Direction, there is a direction from the President of the Republic of Indonesia given to the City of Surabaya to build a waste management installation into electrical energy in accordance with Presidential Regulation Number 35 of 2018 and further direction is given by the Surabaya City Government to the Environmental Service to run the program. 4) Action, the waste management program into electrical energy in the City of Surabaya in collaboration with private agencies according to the specified agreement. 5) Learning, there are environmental experts and ASN who conduct comparative studies abroad to increase their insight into waste management.